Impact of Globalization on India’s Youth: A Systematic Literature Review - Singh, Shweta (Journal of Advanced Research in Humanities and Social Sciences; Vol 12 No 1 (2025): Journal of Advanced Research in Humanities and Social Sciences, 2025)
Globalization, as a dominant force shaping modern society, has had a profound impact on education systems, family structures, youth culture, mental health, and consumption patterns. In developing regions, these changes unfold in distinctive ways, creating a complex narrative that blends both opportunities and challenges. The interaction between global influences and local realities is a critical area of research, offering valuable insights into how youth navigate their aspirations, socio-economic disparities, and cultural transformations. This article aims to examine the effects of globalization on India’s youth by reviewing relevant published research. A total of 93 research articles were initially identified through keyword searches in various databases, which were subsequently narrowed down to 25 articles, forming the final sample based on the study’s objectives. The findings highlight the impact of globalization on various aspects of Indian youth, including education, marriage, mental health, food choices, and leisure activities. The study underscores the importance of strategic policy and program interventions to mitigate negative impacts and enhance the positive outcomes.